ANALISIS POTENSI CADANGAN KARBON UNTUK PENGELOLAAN HUTAN DI TAMAN WISATA ALAM DANAU BUYAN-DANAU TAMBLINGAN - Maku, Bernadina Paulinda; Suarna, I Wayan; Diara, I Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 14 No 2 (2020), 2020)
Taman Wisata Alam (TWA) Danau Buyan-Danau Tamblingan one of the forest ecosystems that are rich in biodiversity.  The information about carbon stocks stored at the surface of the soil is very important to know in order to improvements can be made to the cultivation technique, plant type selection, and right forest management to maintain and increase carbon stocks. The study aimed: calculating and knowing the factors behind the difference carbon stocks above ground level, litter, and soil at Buyan Lake forest and Tamblingan Lake forest and formulating management strategy of TWA Danau Buyan-Danau Tamblingan for supports increased forest carbon stocks. Whereases the measurements carbon stock at medium, low and high density. To formulate management directives used the SWOT analysis. The result of this study is: carbon stocks in above ground level, litter and soil at Buyan Lake forest smaller than Tamblingan Lake forest, with the following details Buyan Lake forest, was: 613.03 ton/ha, 62.56 ton/ha and 125.443 ton/ha whereas Tamblingan Lake forest was: 768.93 ton/ha, 105.26 ton/ha and 360.711 ton/ha, factors causing differences in carbon stocks at Buyan Lake forest and Tamblingan Lake Forest  is the variety of plants that dominate and the human activity.  Management strategy of TWA is: provide assistance to the community to proposing Izin Pengusahaan Pariwisata Alam (IPPA), facilitated indigenous villages to gain recognition of customary forests and formulated awig-awig as local wisdom in management of TWA Danau Buyan-Danau Tamblingan. Keywords: Carbon stock; Forest management strategies; analysis SWOT; TWA Danau Buyan Danau Tamblingan.